Economic performance assessment of residential building retrofits: a case study of Istanbul - Cetiner, Ikbal; Metin, Buket (Springer Science and Business Media LLC, 2017)
This paper presents an approach proposed for assessing economic performance of retrofit applications performed at functional building element level in residential buildings and exemplifies it for the city of Istanbul, which has a temperate-humid climate. This approach covers three steps. In the first step, typical buildings and their properties are determined by analysing the residential buildings in Istanbul, and then the retrofit alternatives are generated. In the second step, an economic impact analysis is performed for typical buildings by considering the costs during their life cycle phases. In the third step, a life cycle cost assessment is done according to the variables, which are defined as window-to-wall ratio (WWR), window system, thermal insulation material, orientation and building age. The most beneficial retrofits are lastly determined depending on their economic performance ratios (EPRs). In conclusion, insulating exterior wall, projected floors, floors above unheated space and roof floors separately provide the highest benefits at the age of 30, and the lowest benefits occur at the age of 15 for all WWRs. The highest EPRs are obtained for the WWR of 10% at all ages. The renewal with PVC frame provides benefit while the renewal with wooden frame causes losses. Orientation slightly affects the EPRs. The use of stone wool in the retrofit causes a reduction in the EPRs due to high investment cost of stone wool. When the 20-year-old building which has the WWR of 10% is insulated with extruded polystyrene and renewed with PVC, it provides the highest benefit of about 45%.